LITERATUR REVIEW: PROMOSI KESEHATAN TERHADAP PELAKSANAAN SCREENING KESEHATAN ANAK USIA PENDIDIKAN DASAR DAMPAK PANDEMI COVID-19 - Ika Harni Lestyoningsih; Winda Soba Diatul Ula (Universitas Negeri Malang, 2022)
AbstractThe Covid-19 pandemic has an impact on optimizing the implementation of health screening for children of primary education age. Through screening activities for children of basic education age (elementary, junior high and high school equivalent). Limited access to information and health services related to social restrictions requires the role of health promotion. The background of this study aims to collect and analyze articles related to health promotion on the implementation of health screening for children of basic education age due to the COVID-19 pandemic. This research method is through a literature review, with the PICO method. Article searches were carried out on four journal search engines namely, Science Direct, Scopus, Google Scholar, and PubMed. Criteria for articles published in the last five years. The results of the literature search show that comprehensive health promotion and education efforts are needed. Some of the literature can provide guidance, information, and knowledge of appropriate health promotion, as an effort to improve health services for children of basic education age. The conclusion is that health promotion has an effect on the implementation of health screening for children of basic education age due to the COVID-19 pandemic, requiring cross-sectoral support and parents.Keywords: health promotion; screening of primary school-age children's health services; the impact of the Covid-19 pandemicAbstrakPandemi Covid-19 berdampak terhadap optimalisasi pelaksanaan screening kesehatan anak usia pendidikan dasar. Melalui kegiatan penjaringan anak usia pendidikan dasar (SD, SMP dan SMA sederajat). Keterbatasan akses informasi dan pelayanan kesehatan terkait pembatasan sosial memerlukan peran promosi kesehatan. Latar belakang penelitian ini bertujuan untuk mengumpulkan dan menganalisis artikel yang berhubungan dengan promosi kesehatan terhadap pelaksanaan screening kesehatan anak usia pendidikan dasar dampak pandemi Covid-19. Metode penelitian ini melalui literature review, dengan metode PICO. Penelusuran artikel dilakukan pada empat search engine jurnal yakni, Science Direct, Scopus, Google Scholar dan PubMed. Kriteria artikel terbitan lima tahun terakhir. Hasil pencarian literatur menunjukkan upaya promosi dan edukasi kesehatan yang komprehensif sangat diperlukan. Beberapa literatur dapat memberikan panduan, informasi dan pengetahuan promosi kesehatan yang tepat, sebagai upaya peningkatan pelayanan kesehatan anak usia pendidikan dasar. Kesimpulannya adalah promosi kesehatan berpengaruh terhadap pelaksanaan screening kesehatan anak usia pendidikan dasar dampak pandemi Covid-19, membutuhkan dukungan lintas sektor terkait dan orang tua.Kata kunci: promosi kesehatan; screening pelayanan kesehatan anak usia pendidikan dasar; dampak pandemi Covid-19